A comparison of mixture and separated-phase models of heat transfer in a stationary wet granular bed. (15th November 2022) - Belekar, Viraj V.; Nere, Nandkishor K.; Sinha, Kushal; Passalacqua, Alberto; Heindel, Theodore J.; Subramaniam, Shankar
Abstract: Solvent removal by thermal drying of granular mixtures is encountered in many industrial operations. A mixture model that treats the granular solid and the liquid solvent along with any interstitial gas phase as a single phase, is a useful first approximation to estimate the time required to heat the system to the wet-bulb temperature at which the solvent starts to vaporize. An analytical solution for the transient, axisymmetric temperature distribution in a stationary wet granular mixture in a heated cylindrical vessel is developed as an approximation to the typical geometry of an industrial dryer . Besides being a good first approximation to obtain an order-of-magnitude estimate of the heating time, the analytical solution serves as an excellent verification case for numerical simulations. A parametric study to assess the effect of fill height and wall temperature on the heating time is performed. Before analyzing the mass transfer aspects of the drying phenomena, it is critical to understand the fundamentals of interphase heat transfer in multiphase mixtures that can be found in such assemblies. Therefore, a 0-D separated-phase (multiphase) heat transfer model is developed to account for the effect of interphase heat transfer in the prediction of heating time of wet granular mixtures in cylindrical vessels. The 0-D model is extended to 3-D simulations using a newly developed OpenFOAM solver with multiphase heat transfer capability. The same problem that was solved using the analytical solution is solved using the 0-D model, and in 3-D using the newly developed OpenFOAM solver, to study the effect of interphase heat transfer on the prediction of heating time. It was found that inclusion of interphase heat transfer in the heat diffusion equations has a significant impact on the predictions of heating time. Further analysis of the problem results in the identification of the non-dimensional thermal interphase transfer number that determines the conditions under which a mixture model can be used in place of a separated phase model in problems involving heat transfer.